Young Adults’ Help-Seeking Experiences in Dealing with Nonsuicidal Self-Injury - Siswanto, Cindy Julistya; Sandjaja, Meilani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Nonsuicidal self-injury (NSSI) is a common mental health issue found among young adults. This study explored the experiences of help-seeking among Indonesian young adults with NSSI, as well as the supporting and inhibiting factors in the process. The approach used in this study is qualitative with a phenomenological research design. NSSI assessments, semi-structured interviews, and photo elicitation techniques were conducted on three participants through purposive sampling with the criteria being aged 18-24 who were indicated to have previously engaged in NSSI. The results of the interpretative phenomenological analysis revealed two themes in the participants’ help-seeking experiences: experiences that initiate seeking help and personal and professional support. Factors influencing help-seeking behavior were also identified, including perceptions of NSSI, perceptions of helpers and received support, public stigma, and social construction. The implications of this research focus on mental health education and the development of mental health service options in addressing negative stigmas and issues related to NSSI.Nonsuicidal self-injury (NSSI) merupakan isu kesehatan mental yang umum ditemui pada dewasa muda. Penelitian ini mengeksplorasi pengalaman mencari bantuan pada dewasa muda di Indonesia dengan NSSI, serta faktor pendukung dan penghambat dalam prosesnya. Pendekatan penelitian ini adalah kualitatif dengan desain penelitian fenomenologi. Dilakukan asesmen NSSI, wawancara semi terstruktur dan teknik photo elicitation pada tiga partisipan melalui purposive sampling dengan kriteria usia 18-24 tahun dan terindikasi pernah melakukan NSSI. Hasil interpretative phenomenological analysis menemukan dua tema dalam pengalaman partisipan mencari bantuan, yaitu: pengalaman yang menginisiasi mencari bantuan dan bantuan personal dan profesional. Ditemukan juga faktor yang memengaruhi perilaku mencari bantuan, berupa: persepsi terhadap NSSI, persepsi terhadap helper dan bantuan yang diterima, stigma publik, dan konstruksi sosial. Implikasi penelitian berfokus pada edukasi kesehatan mental serta pengembangan opsi layanan kesehatan mental dalam menghadapi isu dan stigma negatif terhadap NSSI.